2008
DOI: 10.4049/jimmunol.180.2.1117
|View full text |Cite
|
Sign up to set email alerts
|

The Ischemia-Responsive Protein 94 (Irp94) Activates Dendritic Cells through NK Cell Receptor Protein-2/NK Group 2 Member D (NKR-P2/NKG2D) Leading to Their Maturation

Abstract: Tumor recognition and killing, the uptake of released immunogenic substrate, and the generation of immunity are crucial aspects of dendritic cell (DC)-mediated antitumor immune response. In the context of direct tumoricidal activity, we have recently shown NK cell receptor protein-2 (NKR-P2)/NK group 2 member D (NKG2D) as a potent activation receptor on rat DCs. The activation of DCs with agonistic anti-NKR-P2 mAb, the binding of soluble NKR-P2 to the AK-5 tumor, and DC maturation with fixed AK-5 cells led us … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(42 citation statements)
references
References 82 publications
3
39
0
Order By: Relevance
“…To evaluate the formation of mHSP110-E7 [49][50][51][52][53][54][55][56][57] complex, the purified mHSP110 and FITC labeled E7 [49][50][51][52][53][54][55][56][57] were mixed in a 1:50 molar ratio and incubated in the binding buffer at 55°C for 30 min, followed by incubation at room temperature for 30 min. The complex was then subjected to 10% non-denaturing PAGE analysis.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To evaluate the formation of mHSP110-E7 [49][50][51][52][53][54][55][56][57] complex, the purified mHSP110 and FITC labeled E7 [49][50][51][52][53][54][55][56][57] were mixed in a 1:50 molar ratio and incubated in the binding buffer at 55°C for 30 min, followed by incubation at room temperature for 30 min. The complex was then subjected to 10% non-denaturing PAGE analysis.…”
Section: Resultsmentioning
confidence: 99%
“…here, we investigated mhsp110 as a chaperone immunoadjuvant to enhance the immune response to hpV16 oncoprotein e7-derived CTL epitope e7 [49][50][51][52][53][54][55][56][57] in a mouse model. We developed the hsp110-e7 [49][50][51][52][53][54][55][56][57] complex and demonstrated that mhsp110 could form complexes with peptide e7 [49][50][51][52][53][54][55][56][57] using FITC-labeled e7 [49][50][51][52][53][54][55][56][57] as the tracer. Inoculation of the mhsp110-e7 [49][50][51][52][53][54][55][56][57] complex was capable of priming strong epitope-specific immune response as determined by its ability to elicit an epitope-specific splenocytes proliferation and a cytotoxic T-cell response, and IFNγ production in splenocytes.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations